The Influence of Good Corporate Governance, Free Cash Flow, Leverage and Profitability on Earnings Management in Automotive Sector Companies listed on the Indonesia Stock Exchange - Fitri Yana Sari; Shinta Bella Wijaya; Ninta Katharina (Institute of Computer Science (IOCS), 2022)
The subject of this survey is automotive companies on the IDX. Several companies have studied the value of corporate governance, free cash flow, profitability and results management over the years. This decrease cannot maximize the use of agents and independent auditors in corporate governance, and it is not optimal for companies to use both the shares raised by investors and the shares of the company itself, and the company, resulting in low profits. Leverage, on the other hand, increases in some firms, and an increase in the debt held by firms increases leverage. This means that most of the capital and assets owned by the company are due to its liabilities. The aim of this research is to provide empirical evidence on committee size, audit committee ratios, ownership of independent bodies, manager's ownership, free cash flow, and the impact of debt and profitability on management results. is to get. Survey method by type, type and quantitative research. Quantitative research was chosen as the data collection method. The analysis used is the multiple analysis method. The results of the research show that the size of the audit committee, independent committee, management ownership, net cash flow and leverage ratio have an effect on earnings management in the automotive sector industry which is listed on the BEI. Transactions and profitability owned by institutions partially affect profits on the IDX.